Reduced blood nrf-2 mRNA in local overweight boys at risk of metabolic complications: a study in San Luis City, San Luis, Argentina - Santillán, Lucas Damián (2013)
Background: Childhood overweight (OW) is a matter of public health concern because of its long-term impact on adulthood health. NF-E2–related factor 2 (Nrf-2) regulates the antioxidant/lipogenic response to a sustained positive energy balance that prevails during weight gain. Here we aimed at studying a possible link between OW and Nrf-2–dependent antioxidant/lipogenic response in a local population of boys at risk of metabolic complications. Methods: We measured clinical and biochemical parameters related to lipid metabolism, oxidative stress, and metabolic syndrome in a population of OW boys [body mass index (BMI) percentile ≥85th and <95th, n=22] and normal weight boys (NW; BMI percentile<85th, n=27) from San Luis City, San Luis, Argentina. Results: Compared to NW, OW boys had lower insulin sensitivity, an altered plasma lipid profile, and increased markers of oxidative stress and inflammatory fatty acids. OW boys also had a higher atherogenic index and peripheral insulin resistance than NW boys. We also found that glutathione peroxidase activity and the reduced glutathione to oxidized glutathione ratio were lower in OW boys than NW boys, suggesting that OW boys may have an altered antioxidant response to oxidative stress. Finally, Nrf-2 expression negatively correlated with metabolic syndrome parameters in OW boys. Conclusions: Our data suggest that OW boys have a reduced antioxidant and lipogenic response to a positive energy balance, resulting in oxidative stress, insulin resistance, and risk of developing metabolic complications. Our data also provide a rationale for nutritional interventions aimed at restoring Nrf-2 expression to reduce the risk of metabolic complications in OW boys.